Outcomes, learning, and the curriculum : implications for NVQs, GNVQs, and other qualifications - Burke, John W. (Falmer Press, 1995)
Provides an account of the curricular consequences of the outcomes approach to education NVQs & GNVOs which give a discussion of the main themes leads the reader into a discussion of key ideas and the theory behind the Outcomes approach.